2014
DOI: 10.1186/1754-1611-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Blue and UV LED-induced fluorescence in cotton foreign matter

Abstract: BackgroundCotton is an important domesticated fiber used to manufacture a variety of products and industrial goods. During harvesting with cotton strippers and cotton pickers, it is contaminated with foreign matter from botanical and non-botanical sources which adversely affect the quality and consistency of cotton, and therefore reduces its market value. To improve the current grading done by the High Volume Instrument (HVI) and human inspectors, it was explored whether fluorescence imaging can be used for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Based on the results of a previous study, 11 a total of seven categories of foreign matter optimally excited under UV light were used in the current research (Figure 1). The selected foreign matter included four categories of non-botanical origin (paper, plastic bag, plastic packaging, and twine) and three categories of botanical origin (inner part of seed coat (SCI), outer part of seed coat (SCO), and seed).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of a previous study, 11 a total of seven categories of foreign matter optimally excited under UV light were used in the current research (Figure 1). The selected foreign matter included four categories of non-botanical origin (paper, plastic bag, plastic packaging, and twine) and three categories of botanical origin (inner part of seed coat (SCI), outer part of seed coat (SCO), and seed).…”
Section: Sample Preparationmentioning
confidence: 99%
“…They were closely correlated with the optimal wavelengths presented in the previous study. 11 Therefore, the 19 wavelengths provided the most relevant information regarding the properties of the samples, which could be used for future studies or applications.…”
Section: Selection Of Optimal Wavelengths For Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the spectroscopy technique, the imaging approach can provide spatial information of foreign matter such as size, shape, and spatial distribution of the color (Mustafic et al, 2014). The color imaging systems are inexpensive, relatively easy to build, and therefore have been intensively investigated previously to detect cotton FM.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its success, this study only investigated non-botanical FM and another limitation of the system was that this color-imaging system can only detect FM with distinct colors. To overcome this limitation, Mustafic et al (2014) developed a fluorescence imaging system to identify twelve types of cotton FM excited under blue and UV LED. Results showed that there were different levels of fluorescence among the twelve FM and cotton lint, and fluorescence imaging could be effective in detecting FM with similar color but different fluorescence emissions.…”
Section: Introductionmentioning
confidence: 99%